Alteration of lymphocyte phenotype and function in sickle cell anemia: Implications for vaccine responses. Issue 9 (14th July 2016) - Balandya, Emmanuel; Reynolds, Teri; Obaro, Stephen; Makani, Julie
Abstract : Individuals with sickle cell anemia (SCA) have increased susceptibility to infections, secondary to impairment of immune function. Besides the described dysfunction in innate immunity, including impaired opsonization and phagocytosis of bacteria, evidence of dysfunction of T and B lymphocytes in SCA has also been reported. This includes reduction in the proportion of circulating CD4+ and CD8+ T cells, reduction of CD4+ helper: CD8+ suppressor T cell ratio, aberrant activation and dysfunction of regulatory T cells (Treg ), skewing of CD4+ T cells towards Th2 response and loss of IgM‐secreting CD27 + IgM high IgD low memory B cells. These changes occur on the background of immune activation characterized by predominance of memory CD4+ T cell phenotypes, increased Th17 signaling and elevated levels of C‐reactive protein and pro‐inflammatory cytokines IL‐6 and TNF‐α, which may affect the immunogenicity and protective efficacy of vaccines available to prevent infections in SCA. Thus, in order to optimize the use of vaccines in SCA, a thorough understanding of T and B lymphocyte functions and vaccine reactivity among individuals with SCA is needed. Studies should be encouraged of different SCA populations, including sub‐Saharan Africa where the burden of SCA is highest. This article summarizes our current understanding of lymphocyte biology in SCA, and highlights areas that warrant future research. Am. J. Hematol. 91:938–946, 2016. © 2016 Wiley Periodicals, Inc.